CARCASS YIELDS AND ORGANS OF BROILERS FED THE DIET CONTAINING THE FERMENTED MORINGA LEAF MEAL + YELLOW CORN - zulfan zulfan; Muhammad Aman Yaman; zulfikar zulfikar; Asmaul Husna; Jaunda Fitra (Jurnal Kedokteran Hewan, 2022)
The purpose of this study was to evaluate the characteristics of carcass yields and internal and external organs of the broilers fed the diets containing the fermented moringa leaf meal (FMOL) + yellow corn (YC), the moringa-corn (MC) diet formulated to replace parts of the commercial diet (CD). As many as 100 DOC of broiler chicken strain CP 707 were reared for up to 5 weeks to feed experimental diets. A Block Randomized Design (BRD) with subsamples consisted of 4 treatments, 5 blocks, and 2 subsamples were applied in the recent study. The results of studies indicated that removing parts of the CD diet to substitute with the mixture of FMOL + YC caused a significant effect (P0.05) in declining the weights of the whole carcass and the cut-ups but in percentage no significant differences. The weights and percentages of all examined organs were not significantly affected (P0.05). It was concluded that using the moringa mixed with yellow corn reduced the weight of the whole carcass and cut-up carcasses but it could use up to 7.5% in the diet without detrimental effects on the internal and external organs of the broilers.